Pelatihan Digital Marketing sebagai upaya peningkatan Pendapatan Bagi UMKM di kabupaten MBS - Tyahya Whisnu Hendratni (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2021)
This community service activity aims to increase understanding of digital marketing for MSMEs in the MBS district. By maximizing the use of online media, it can increase business competitiveness. For MSME players, adequate online media knowledge and quality content can be used to market their products. This situation is very influential, significantly since the Covid 19 pandemic that has hit Indonesia since March 2020 has changed the way people meet their daily needs. Consumers who used to shop directly are now experiencing changes by using digital transactions. Marketing online through social media provides opportunities for MSME to interact with consumers. The approach method used is for active MSMEs. The method is done by providing counseling online through zoom media. This service activity was carried out orderly and smoothly. The participants were very enthusiastic about listening to the speakers’ presentations. The attendance of the participants proves this right from the beginning of the event to the end of the event. It is hoped that training and the service team can assist MSMEs so that they can monitor the progress of increasing sales turnover. Keywords : Digital Marketing, Increase in UMKM income, Training Via Zoom